Resonant converter topology with losses compensation for the ISOLDE/CERN modulator - Redondo, Luis (2019)
This paper describes a solid-state asymmetric bridge resonant topology to increase the energy efficiency of switching pulse modulators. The solid-state resonant topology will replace an existing pulse transformer and thyratron-based resonant modulator to supply the 60-kV target potential for the ion acceleration of the On-Line Isotope Mass Separator ISOLDE accelerator. An experimental prototype is tested in order to validate the proposed concept, including a low auxiliary voltage power supply to compensate the losses in the circuit. The design of the circuit components and the experimental results for a 6-kV prototype are presented and discussed, as well as the design procedure and parameters for the 60-kV modulator, including a high-voltage gapped coil core.